A New Iterative Elliptic PDE Solver On A Distributed Pc Cluster. - Mohd. Ali, Norhashldah; Ng, Kok Fu (2008)
Advancement in parallel computers technology has greatly influenced the numerical methods used for solving partial differential equations (pdes). A lot of attention has been devoted to the development of .numerical schemes which are suitable for the parallel environment.